Potential Use of Mosquito’s Salivary Components as Novel Target for The Development of Transmission Blocking Vaccine (TBV) - KARTIKA SENJARINI (Microbiology Indonesia, 2013)
Mosquito-borne diseases are rampant in most tropical regions of the world, especially rural, forested, and coastal  areas  such  as  Indonesia.  Despite  long-standing  chemotherapeutic intercession  and  vector  control programs, mosquito-borne diseases exact a heavy burden on human health  in Indonesia. Two major public health problems  transmitted by mosquito  in Indonesia are malaria and dengue haemorrhagic fever (DHF), causing millions of clinical episodes occurring annually. Malaria is now recognized as a serious re-emerging threat to public health. DHF cases were first observed in 1968; since then, the incidence has been constantly increasing and the disease is now one of the principal causes of child lethality. It has been widely observed that saliva of mosquito  that  transmits  the diseases contains several factors  that could enhance pathogen  infection. Therefore,  it should be possible  to control pathogen  transmission by vaccinating  the host against  the molecule(s)  in saliva  that potentiate  the  infection. However, specific component as a potential  target  for TBV  in mosquito vectors of malaria & dengue,  i.e. Anopheles and Aedes aegypti, has not been  identified so  far. This paper wanted  to elaborate the potential role of salivary component from mosquitoes, particularly from Indonesian vectors as molecular target  for developing TBV against  two major Mosquito borne-diseases  in  Indonesia  i.e. malaria and DHF.